PRELIMINARY STUDY OF ANTIOXIDANT ACTIVITY OF DRAGONFRUIT, DATES AND KEFIR MIXTURES - Ajrina, Amalia (Faculty of Vocational Studies, Universitas Airlangga, 2022)
Background: Some previous studies showed that either dragon fruit, dates, or kefir has antioxidant activity. Nevertheless, there has not been any study that showed the activity of the combination of those three elements. Purpose: Therefore, the main purpose of this study is to examine the best combination of dragon fruit, dates, and kefir as an antioxidant activity. Method: The combination variation includes: dragon fruit-dates, dragon fruit-kefir, kefir-dates, and dragon fruit-dates-kefir. Then, the antioxidant activity was tested using the DPPH assay. Result: The variation of dragon fruit and dates, the highest value of antioxidant activity was obtained from the combination of 10: 2 of dragon fruits: dates; that was 76.33 ± 0.27 mg/dL. The combination of dragon fruit and kefir, the highest value was obtained from the variation of 10: 4 of dragon fruit: kefir. For this variation, the antioxidant activity was 80.9 ± 0.4 mg/dL. The combination of kefir and dates, the highest value was obtained from the variation of 10: 3 of kefir: dates. The combination of dragon fruit, dates, and kefir, the highest value of antioxidant activity was obtained from the combination of 4: 10: 1 of dragon fruit: kefir: dates; that was 80.94 ± 0.4 mg/dL. Conclusion: In summary, the highest antioxidant activity came from the combination variation of 4: 10: 1 of dragon fruit: kefir: dates.